Facebook, a mídia e a democracia: big tech, estado pequeno - Felix Nascimento, Reginaldo; Maria Santana Nascimento, Cristiana; Maria Santana Nascimento, Cristiana; Flávio Oliveira Amorim, Aldo (diké, 2025)
Resenha ANDREWS, Leighton. Facebook, The Media and Democray: Big Tech, Small State. Routledge Focus, 2020.